2013
DOI: 10.1093/bja/aet022
|View full text |Cite
|
Sign up to set email alerts
|

Systemic vascular resistance has an impact on the reliability of the Vigileo-FloTrac system in measuring cardiac output and tracking cardiac output changes

Abstract: These results indicate that the reliability of the Vigileo-FloTrac system to measure CO and track changes in CO induced by phenylephrine administration was not clinically acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…2). Similarly, we have previously [10] reported that the percentage error with normal ventilated patients was acceptable only for normal SVRI. Sotomi et al [20] studied cardiac surgery patients and found a high percentage error (60.3 %); however, in a sub-analysis based on SVR, they noted a relatively satisfactory concordance in normal SVR patients regardless of vasoactive agent use.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…2). Similarly, we have previously [10] reported that the percentage error with normal ventilated patients was acceptable only for normal SVRI. Sotomi et al [20] studied cardiac surgery patients and found a high percentage error (60.3 %); however, in a sub-analysis based on SVR, they noted a relatively satisfactory concordance in normal SVR patients regardless of vasoactive agent use.…”
Section: Discussionsupporting
confidence: 70%
“…Many studies have reported about the bias between APCO and ICO under various circumstances, which are summarized in Table 3 [10,[17][18][19][20][21]. Akiyoshi et al [17] has investigated about the ability of Vigileo TM -FloTrac TM system to measure CO in liver transplant surgery patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in numerous validation studies, when the vascular tone was assigned a severe condition such as vasoplegia (septic shock) or when vasoactive drugs were infused, the cardiac output values provided by this technique lacked precision [59]. Therefore, the use of this technology in ICU patients in shock is cautioned and cannot be considered as a reference method [60].…”
Section: Ap (Mmhg)mentioning
confidence: 99%